Levels of the EMT‐related protein Snail/Slug are not correlated with p53/p63 in cutaneous squamouscell carcinoma. (23rd March 2013) - Chen, Hongxiang; Takahara, Masakazu; Xie, Lining; Takeuchi, Satoshi; Tu, Yating; Nakahara, Takeshi; Uchi, Hiroshi; Moroi, Yoichi; Furue, Masutaka
<x xml:space="preserve">Abstract</x> Background The contribution of the E‐cadherin transcriptional repressors Snail and Slug to invasion and metastasis has strengthened the evidence for the importance of epithelial‐mesenchymal transition (EMT) in carcinoma progression. However, to the best of our knowledge, no study has described the immunohistochemical staining of the EMT‐related proteins Snail/Slug in skin tumors and the correlation between Snail/Slug and tumor suppressor p53/p63. Methods We performed immunohistological staining of Snail, Slug, E‐cadherin, p53 and p63 in 20 archived specimens each of seborrheic keratosis (SK), actinic keratosis (AK) and squamous cell carcinoma in situ (SCCIS), and 53 specimens of cutaneous squamous cell carcinomas (SCC). Fifteen normal skin (NS) specimens served as controls. Results Significant negative correlations were observed between Snail and E‐cadherin expression and between Slug and E‐cadherin expression (Snail: R2 = 0.5432, p < 0.01; Slug: R2 = 0.4666, p < 0.01). Conclusions The staining intensities of Snail and Slug are associated with decreased E‐cadherin staining in SCC and this may promote EMT. However, the staining intensities of p53 and p63 are not significantly correlated with the loss of E‐cadherin.